Aid-Dependency and Attributes of an Aid-Exit Strategy - Admasu Shiferaw; Degol Hailu (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2010)
This paper tracks a group of developing countries which started off in the 1960s with a comparable and relatively high aid dependency but followed two different paths in the subsequent four decades: where one sub-group of countries became increasingly aid dependent while the other sub-group nearly exited aid-dependency. It then compares the trajectories of key macroeconomic variables in the two groups of countries in a bid to provide broad sketches of an aid-exit strategy. The paper shows that the likelihood of exiting aid dependency increases with the rate of investment and the share of manufacturing in GDP while it declines with the size of the saving-investment gap and the rate of inflation.
Keywords: F35; O16; 330; Aid Dependency; Aid Exit; Investment; Domestic Saving; Inflation